Mulch and groundcover effects on soil temperature and moisture, surface reflectance, grapevine water potential, and vineyard weed management - Bavougian, Christina M.; Read, Paul E. (PeerJ, 2018)
The objectives of this research were to identify alternatives to glyphosate for intra-row (under-trellis) vineyard floor management and to evaluate the potential for intra-row and inter-row (alleyway) groundcovers to reduce vegetative vigor of ‘Marquette’ grapevines (Vitis spp.) in a southeast Nebraska vineyard. The experiment was a randomized factorial design with five intra-row treatments (crushed glass mulch [CG], distillers’ grain mulch [DG], creeping red fescue [CRF], non-sprayed control [NSC], and glyphosate [GLY]) and three inter-row treatments (creeping red fescue [CRF], Kentucky bluegrass [KB], and resident vegetation [RV]). Treatments were established in 2010–2011 and measurements were conducted during 2012 and 2013 on 5- and 6-year-old vines. Soil temperatures were mostly higher under mulches and lower under intra-row groundcovers, compared to GLY. Weed cover in CG, DG, and CRF treatments was the same or less than GLY. At most sampling dates, inter-row soil moisture was lowest under KB. Intra-row soil moisture was highest under DG mulch and lowest under CRF and NSC; CG had the same or lower soil moisture than GLY. Surprisingly, we did not detect differences in mid-day photosynthetically active radiation (PAR) reflectance, despite visual differences among the intra-row treatments. Mid-day vine water potential did not differ among treatments. We concluded it is not necessary to maintain a bare soil strip under established vines in this region, where soil fertility and moisture are non-limiting.
Keywords: Vineyard floor management; Groundcover; Mulch; Weed control; Glyphosate; Vegetative vigor